PENGARUH KONVERGENSI IFRS, BONUS PLAN, DEBT COVENANT, DAN POLITICAL COST TERHADAP KONSERVATISME AKUNTANSI - Reskino Reskino; Ressy Vemiliyarni (Akuntabilitas, 2014)
This research aims to analyze and get empirical evidence about the effect of IFRSconvergence, bonus plan, debt covenant, and political cost on accounting conservatism incompanies which are listed at BEI. Independent variables in this research are IFRSconvergence, bonus plan which is proxied by the structure of managerial ownership, debtcovenant which is proxied by leverage, and political cost whichis proxied by firm size.Dependent variable in this research is accounting conservatism. Sample used in this researchare companies which are listed at BEI in 2012. By using purposive sampling, found that 127companies are proper sample of the research. The multiple regression analysis is the methoduse to analyse the hypotesis. The results shows that IFRS convergence and political cost havenegative effect and significantly on accounting conservatism. On the other hand, bonus planand debt covenant didn’t effect significantly on accounting conservatismDOI: 10.15408/akt.v7i3.2736